Short-term intervention complemented by wearable technology improves Trichotillomania – A naturalistic single-case report - Leibinger, Konstantin W.; Murray, Eileen; Aschenbrenner, Steffen; Randerath, Jennifer (Frontiers in Psychology, 2023)
There is a growing interest in using wearable technology for the treatment of body-focused repetitive behaviors (BFRBs), such as Trichotillomania. Yet, to our knowledge, few studies address the applicability and use of wearable technology as a therapeutic element in more naturalistic situations. Here we would like to introduce its potential use combined with a Habit-Reversal Training in a single-case experimental design. In practice, individuals with BFRBs frequently show complex constellations of psychiatric disorders. Accordingly, the here presented participant was diagnosed with Trichotillomania as well as comorbid ADHD and examination phobia. The participant was offered to wear an unobtrusive and user-friendly vibration device that sent an alarm when her critical hairpulling behaviors occurred. The complementing Habit-Reversal Training included an Awareness Training supported by the vibration alarm of the wearable device. It further included a Competing Response Training by learning benign behaviors that could replace the hairpulling behavior. The frequency of hairpulling episodes was assessed using daily self-reports and by using the monitoring function of the wearable device. The intervention procedure was implemented into the participant’s everyday life and evaluated over the course of 214 days. The results indicated a significant reduction in the daily episodes of hair pulling. Our preliminary findings suggest that the here applied intervention has the potential to effectively treat Trichotillomania in individuals with comorbid disorders in psychotherapeutic outpatient care. Certainly, group-studies will need to further validate the approach’s effectiveness.